STABILITY ANALYSIS AND ERROR ESTIMATES OF LOCAL DISCONTINUOUS GALERKIN METHOD FOR CONVECTION-DIFFUSION EQUATIONS ON OVERLAPPING MESH WITH NON-PERIODIC BOUNDARY CONDITIONS - Chuenjarern, Nattaporn; Wuttanachamsri, Kanognudge; Yang, Yang (My University, 2021)
A new local discontinuous Galerkin (LDG) method for convection-diffusion equations on overlapping meshes with periodic boundary conditions was introduced in [14]. With the new method, the primary variable u and the auxiliary variable p = ux are solved on different meshes. In this paper, we will extend the idea to convection-diffusion equations with non-periodic boundary conditions, i.e. Neumann and Dirichlet boundary conditions. The main difference is to adjust the boundary cells. Moreover, we study the stability and suboptimal error estimates. Finally, numerical experiments are given to verify the theoretical findings.
Keywords: Error analysis; Local discontinuous Galerkin method; Overlapping meshes; Stability